Textbook of sports and exercise cardiology (Springer Nature, 2021)
This textbook provides a comprehensive, yet practically orientated overview of classic and novel sports cardiology topics, based on current evidence, guidelines, recommendations and expert experience. Numerous publications have provided guidance to these issues, but it has become increasingly difficult for both students and doctors to obtain a thorough, but practicable overview for optimal clinical care of athletes and patients. This book is intended as an educational work, filling the large gaps that are still present in the current educational guidelines for medical students and cardiology trainees.